TEACHING SYNONYMIES IN LANGUAGE CLASSROOM THROUGH LITERATURE. (JANE EYRE) - Jamila Ermetova; Matkarimova Malika Oybek qizi (Journal of new century innovations, 2023)
Annotation: English has been used in Uzbekistan as a second language after Independence. There are many aims of teaching and learning English, but the most important reason is English is a one of global languages. English is considered the link between different countries and people who speak different languages. It is mostly used in trade, meetings, medicine, technology, education, and science. Besides, English is mostly being chosen for its several, rich literatures, arts, movies, and songs. Especially, teacher prefer them to attract second-language learners’ attention. Literature is not only best way of educating vocabulary, grammar, spelling, but also culture. Many people think that literature is most powerful and motivating source of learning vocabulary and writing. When students enjoy the learning process, learning vocabularies is not challenging for them at lot. Wide range of vocabularies, expressions, idioms and their alternatives are used in literature. If second-language students are only used old and big dictionaries and taught grammar books in the classroom, it is not effective at all as well as they can lose their interests towards the language. Using literature in ELT classrooms can be beneficial to increase number of vocabularies, synonymies and antonymous of learners.